Perancangan Aplikasi Mobile untuk Penyewaan Lapangan Olahraga dengan Metode Backend for Frontend - Tjokra, Cindy Vanesya; Sediyono, Eko (Jurnal Teknik Informatika dan Sistem Informasi, 2025)
This study aims to design a mobile-based sports field rental system by applying the Backend for Frontend (BFF) architectural approach. The main problem addressed is the limitation or manual systems in terms of efficiency, schedule transparency. And ease of booking. The research was conducted through several stages, including data collection, user interface design using Figma, backend development using Laravel, and API endpoint testing via Postman. The system evaluation was based on the ISO/IEC 25010 standard, particularly focusing on functional suitability, performance efficiency, reliability, and maintainability. The test results show that all endpoints responded correctly, with an average response time ranging from 200 to 600 ms, and no server errors were found. These findings indicate that the Backend for Frontend BFF approach is effective in supporting a modular and efficient digital rental system that is ready for integration into mobile applications.